Presence, abundance and associability of Citronella mucronata in secondary forests dominated by Nothofagus obliqua in the foothills of Curicó, Maule Region, Chile - Corvalán, Patricio; Galleguillos, Mauricio; Hernández, Jaime (Bosque (Valdivia), 2017)
In Chile, Citronella mucronata is a tree species classified as "nearly endangered", highlighting the lack of quantitative information about their populations. The aim of this study was to provide knowledge about C. mucronata populations in secondary forests of Nothofagus obliqua in the Andes foothills of Maule region, central Chile. Specifically the goal was to examine the presence, abundance and associability of C. mucronata and its relation to landscape variables of the Andes foothills. A forest inventory was conducted with the setup of 197 clusters with five plots each. Moreover, a computation of a high resolution geomorphological index was obtained based on LiDAR remote sensing, which allowed establishing geographical distribution patterns of the species. In the sampling area, C. mucronata was present in 31.1%, the average abundance was 117 trees per hectare and the mean altitudinal distribution was 1.149 m a.s.l. with a 142 m interquartile range of the altitude reached preferably in well-drained areas as evidenced by the landform index values. Citronella mucronata was slightly associated with Aextoxicon punctatum, Aristotelia chilensis, Austrocedrus chilensis, Azara petiolaris, Cryptocarya alba, Laurelia sempervirens, Lomatia dentata, Luma apiculata, Maytenus boaria, Nothofagus obliqua, Persea lingue, Podocarpus salignus and Quillaja saponaria and not associated with Drimys winteri, Escallonia pulverulenta, Lithraea caustica, Lomatia hirsuta or Myrceugenia exsucca. Their density shows no significant correlation with the density of any other species. The study allowed deepening knowledge of the species in secondary forests of N. obliqua.